All the Missing Girls - Miranda, Megan (Waterville, Maine : Wheeler Publishing, 2016)
"Ten years after leaving Cooley Ridge, Nicolette Farrell returns to care for her ailing father. A decade ago, she, her brother Daniel, her boyfriend Tyler, and Corinnes boyfriend Jackson were suspects when Corinne-- Nics best friend-- disappeared without a trace. Within days of Nics return, they are plunged into a shocking drama when Nics neighbor Annaleise, who is dating Tyler and was the groups alibi ten years previously, goes missing. Told backwards from the time Annaleise disappears, the book follows Nic as she works to unravel the truth and, in the process, reveals shocking realities about her friends, her family, and what really happened to Corinne that night ten years ago" --
Keywords: Missing persons -- Investigation; Fiction; Cold cases (Criminal investigation) -- Fiction; Small cities -- Fiction; Friendship -- Fiction; Missing persons -- Investigation; Fiction; Thrillers (Fiction); Large type books